Combining ability and heterosis for some canola characteristics sown on recommended and late planting dates using biplot - Hassan AMIRI OGHAN; Farnaz SHARIATI; Naser SABAGHNIA; Bahram ALIZADEH; James MILLNER; Amir Hossein SHIRANI RAD; Majid GHOLAMHOSEINI (Acta Agriculturae Slovenica)
Canola (Brassica napus L.) is one of the most efficient oil-producing crops in arid and semi-arid regions of the world. In the current study, ten winter canola genotypes [seven genotypes as lines (Zarfam (L1), Talaye (L2), SLM046 (L3), Geronimo (L4), Modena (L5), Opera (L6) and Symbol (L7)] and three genotypes as testers [Okapi (T1), Licord (T2) and Orient (T3)] and their F1 hybrids (21 hybrids) were evaluated to determine the genetic parameters for grain yield, oil content, meal and seed glucosinolate contents under two different planting date [recommended (late September) and late planting (late October)]. According to combined analysis of variance there were significant differences among the genotypes for most studied traits. The genotype main effect and genotype × environment interaction (GGE) biplot method was used for analyzing line × tester design data. Among the lines, L5 showed high negative general combining ability (GCA) effect for meal glucosinolate content in both conditions whereas L1, L5 and L6 revealed high negative GCA effects for seed glucosinolate content in both planting date. From the results, it could be concluded that, hybridization between T1×L1, T1×L6 or T3×L5 is an efficient approach to release genotypes with low seed and meal glucosinolate content. Furthermore, to develop canola cultivars with higher seed and oil yield, hybridization between T1×L7 or T2×L7 is highly recommended. Improved oil content will be achieved if T1×L5, T2×L5 or T3×L6 hybrids are implemented into the breeding programs.